1983
DOI: 10.1128/aem.46.3.666-672.1983
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and total mineralization of monohalogenated biphenyls in natural sediment and mixed bacterial culture

Abstract: Mixed bacterial cultures obtained from polychlorinated biphenyl-contaminated river sediments are capable of degrading monohalogenated biphenyls under simulated natural conditions. Culture conditions include river water as supportive medium and mixed bacterial cultures obtained from river sediments. Degradation occurs when the substrates are supplied as the sole carbon source or when added together with glucose. The degradation rates of 2-, 3-, and 4-chlorobiphenyl, at 30 jig ml-', were 1.1, 1.6, and 2.0 ,ug ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…Quantification of 4CB mineralization. Liberation of 14CO2 from the U-14C-chlorophenyl ring-labeled 4CB was used to measure total mineralization as described previously (18). Bacterial growth conditions, assay methods, and collection of 14CO2 were as described previously (18) with the following exceptions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantification of 4CB mineralization. Liberation of 14CO2 from the U-14C-chlorophenyl ring-labeled 4CB was used to measure total mineralization as described previously (18). Bacterial growth conditions, assay methods, and collection of 14CO2 were as described previously (18) with the following exceptions.…”
Section: Methodsmentioning
confidence: 99%
“…Because of their unreactive chemical structure and low water solubility, they generally are considered to be nondegradable (16). Despite this, there have been several reports of PCB degradation in mixed (4,11,13,18,24) and pure (1,14,20,23,26) bacterial cultures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorinated benzoic acids have a role in regulating bacterial PCB degradation; hence for significant degradation of PCBs to occur in the environment there is the requirement for the presence of organisms possessing genes encoding both the upper pathway (PCB degradation) and the lower pathway (chlorobenzoate degradation). In an attempted simulation of a natural river environment, Kong and Sayler (1983) showed that all .nonochlorinated and monobrominated biphenyls were degraded at low concentrations. Degradation occurred through the corresponding halogenated benzoates.…”
Section: Biorel1zediation Ofpcbs 169 Mineralizatiolt Of Pcbs By Nlicmentioning
confidence: 99%
“…Although several mixed-culture populations have been shown to be capable of the mineralization of 4-chlorobiphenyl to carbon dioxide and water ([79,84] for only the unchlorinated ring; [112] first report of mineralization of chlorinated ring), no single species had been shown to be capable of 4-chlorobiphenyl complete mineralization until the work of Sayler et al [113]. Pure cultures were isolated from the mixed community described by Kong and Sayler [112]. These communities were capable of the complete degradation of monochlorinated and monobrominated biphenyls to C 0 2 and water.…”
Section: Biodegradationmentioning
confidence: 99%